2020
DOI: 10.4314/ahs.v20i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic susceptibility pattern of bacteriuria among HIV-seropositive patients attending the Bamenda Regional Hospital, Cameroon

Abstract: Background: HIV causes a decrease in CD4+ lymphocyte cells count, exposing the individual to infections (urinary tract infections). This study was carried out to determine the prevalence of bacteriuria and antimicrobial susceptibility pattern of bacteria isolates among HIV patients. Methods: Clean catch mid-stream urine samples were collected from 135 HIV- seropositive patients, cultured on Cystein lactose electrolyte deficient (CLED) agar and incubated at 370C for 24 hours. The modified Kirby-Bauer’s di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
2
2
Order By: Relevance
“…The finding of our study is lower than study conducted in cameroon (67.4%) [34], 27.7% in Nigeria [35] and other study in nigeria 25.3% [36], 40.5% in Nigeria [37]. This could be because in previous studies, nearly half of the study participants [34] had less than 200 CD4 counts, whereas in our study, only one fifth of the study participants had less than 200 CD4 counts, indicating that our study participants' immune status was relatively intact compared to the previous one [38]. Study participants with excellent immunity are less likely to get a…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The finding of our study is lower than study conducted in cameroon (67.4%) [34], 27.7% in Nigeria [35] and other study in nigeria 25.3% [36], 40.5% in Nigeria [37]. This could be because in previous studies, nearly half of the study participants [34] had less than 200 CD4 counts, whereas in our study, only one fifth of the study participants had less than 200 CD4 counts, indicating that our study participants' immune status was relatively intact compared to the previous one [38]. Study participants with excellent immunity are less likely to get a…”
Section: Discussioncontrasting
confidence: 93%
“…Here in our study, those males who are living with HIV have a lower risk of UTI than females (OR:0.35, 95% CI: 0.14, 1.02), although the difference is not statistically significant. It had statistically significant association [26], Participants with CD4 counts more than 200 showed a decreased risk of UTI than those with CD4 counts less than 200 (OR:0.36, 95% CI: 0.06, 2.35) but not statistically significant association in our study although having statistically significant association in a study conducted in Cameroon [34]. In addition to the above, those study participants who have never had a catheterization have a lower risk of obtaining a UTI than those who have (OR: 0.35, 95% CI: 0.06, 1.86) because Catheters put into the bladder cause nosocomial urinary tract infection (UTI) by allowing direct inoculation of microorganisms into the bladder during insertion or during post-insertion manipulation of the catheter PLOS ONE or its drainage system.…”
Section: Plos Onecontrasting
confidence: 65%
“…10,11 However, even higher gures were quoted from Saudi Arabia (32.1%) Iraq (42.9%) and Nigeria (37.1%). 12,13,14 Frequency as low as 3.3% has been quoted from India. 15 16,17,18,19 Another study has shown an upward trend of ASB among multiparous women of advanced age.…”
Section: Variablesmentioning
confidence: 99%
“…From Cameroon we have work on antibiotic susceptibility among HIV-seropositive patients attending a regional hospital 6 . Work from Uganda's remote Karamoja region gives us a glimpse into capacity assessment for provision of quality sexual reproductive health and HIV-integrated services 7 .…”
Section: Infectious Diseasesmentioning
confidence: 99%